Empirical analysis of influencer attributes and social satisfaction effects on purchase intentions in chinese social media - Yifan Yao; Dongxia Meng; Xiaoguang Wei (Scientific Reports)
Abstract Underpinned by attribution theory and source credibility theory, this study investigates how influencer characteristics and customer’s prior product knowledge affect purchase decisions in the context of social media marketing. A conceptual model incorporating nine potential antecedents was developed based on identified research gaps. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were conducted using data from an online survey of 363 respondents who follow entertainment-type influencers. Results reveal that social satisfaction mediates the relationship between influencer characteristics and purchase intention, while customers’ product knowledge moderates this mediated relationship. Specifically, visual aesthetics and denotative inspiration significantly influence social satisfaction, whereas influencer level and connotative inspiration show no significant effects. The study contributes to the theoretical understanding of influencer marketing by integrating attribution theory in a digital context, particularly within the Chinese market. These findings offer practical insights for businesses and marketers in optimizing influencer selection and content strategies, with particular relevance for the rapidly evolving Chinese social media landscape.